Comparison of the effects of hyperbaric oxygen and extracorporeal shock wave therapy on healing in osteotendinousjunctional injuries: an experimental study of the rabbit model - Halil, Bilgin; Özkan, Yüksel; Akalın, Yavuz; Çevik, Nazan; Öztürk, Alpaslan (The European Research Journal, 2020)
Objectives: To biomechanically and histopathologically compare the effects on healing in the osteotendinous region of the treatment methods of hyperbaric oxygen (HBO) and extracorporel shock wave (ESW) on an injury created at the osteotendinous junction in an experimental rabbit model.Methods: The study included 36 New Zealand rabbits.The patellar tendon tibial osteotendinous junction was cut and then repaired. Group 1 was evaluated as the control group, with no further intervention.In Group 2, a single session of ESW was applied at 14 hz/750 Impulse/10 mins to an area 1×1 cm2 in the repaired area under fluoroscopy guidance. The animals in Group 3 were applied with 100% oxygen as HBO at 2.4 ATA/110 min for 7 days. At the end of 6 weeks, 6 animals from each group were applied with a tension test and 6 animals were processed for histopathological examination.Results: In Group 1, the forces at the start of the separation of the osteotendinous junction, at a 2 mm separation and at full rupture were lower than those of Group 2 and Group 3 (p = 0.001 and p = 0.001, respectively). The highest separation force values were determined in Group 3 (p = 0.001). Histopathologically, a statistically significant difference was determined in respect of the fibrocartilage tisssue formation, and fusion with new bone tissue between Group 1 and Group 2 and between Group 1 and Group 3 (p < 0.05). No statistically significant difference was determined between Group 2 and Group 3 (p = 0.310). Conclusions: It was observed that the application of HBO and ESW improved biomechanical resistance and healing in the injuries in the osteotendinous junction by increasing the bone-tendon fusion in this area.The application of HBO and ESW increased biomechanical resistance compared to the control group.In the histopathological evaluation, the ESW group was better than the control group and the HBO group was evaluated as the best.